2016
DOI: 10.3892/or.2016.5299
|View full text |Cite
|
Sign up to set email alerts
|

Gigantol attenuates the proliferation of human liver cancer HepG2 cells through the PI3K/Akt/NF-κB signaling pathway

Abstract: Gigantol is a phenolic substance extracted from plants in the genus Dendrobium and used in traditional Chinese medicine. In the present study, we aimed to investigate the growth inhibition and apoptotic effects of gigantol on human liver cancer cells through the PI3K/Akt/NF-κB signaling pathway. HepG2 cells were treated with different concentrations of gigantol (0-150 µM) for 12, 24 and 48 h. It was found that gigantol significantly inhibited the proliferation and induced apoptosis of the HepG2 cells. The resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
40
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 43 publications
(48 citation statements)
references
References 32 publications
4
40
0
Order By: Relevance
“…Phenols derived from natural plants contain numerous antioxidants and therefore are typically used to study antioxidative activities (8)(9)(10)(11). Furthermore, gigantol is reported to exhibit numerous biological functions, including anti-osmosis effects (12), antitumor effects in human liver (13) and lung (14) cancer, antimutagenic effects (15) and immunomodulatory activities (16). Additionally, gigantol was reported to be a potent compound for restoring sight in diabetics with cataracts (17).…”
Section: Introductionmentioning
confidence: 99%
“…Phenols derived from natural plants contain numerous antioxidants and therefore are typically used to study antioxidative activities (8)(9)(10)(11). Furthermore, gigantol is reported to exhibit numerous biological functions, including anti-osmosis effects (12), antitumor effects in human liver (13) and lung (14) cancer, antimutagenic effects (15) and immunomodulatory activities (16). Additionally, gigantol was reported to be a potent compound for restoring sight in diabetics with cataracts (17).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, phosphorylation of Akt, the downstream effector of PI3K, has been observed as a critical mediator in the NF-κβ signaling pathway promoting cell proliferation and protecting cancer cells against apoptosis in cancer cells [17]. Previous studies demonstrated that PI3K/Akt/NF-κβ signaling pathway was a crucial target in the mechanism investigation of therapeutic route in various cancer cells [18-20]. However, the detailed mechanisms of PI3K/Akt/NF-κβ signaling pathway and with the relationship to apoptosis of cancer are still unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have reported the potential anti-cancer activities of gigantol, one of the most widely studied bibenzyls. Gigantol has exhibited cytotoxicity against various types of cancer cells, such as breast, liver, and lung cancer cells [24,32,33]. Moreover, gigantol could attenuate certain aggressive phenotypes that bring about tumor progression and metastasis, including proliferation, migration, invasion, anoikis-resistance, and anchorage-independent growth [25][26][27][28].…”
Section: Discussionmentioning
confidence: 99%